2010
DOI: 10.1016/j.ghir.2010.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between oral contraceptive status and GSTM1 and GSTT1 deletions on insulin-like growth factor-1 (IGF-1) plasma levels in young healthy women

Abstract: Access to the published version may require journal subscription. Published with permission from: ElsevierInteractions between oral contraceptive status and GSTM1 and GSTT1 deletions on insulin-like growth factor-1 (IGF-1) plasma levels in young healthy women Abstract Objective: Insulin-like growth factor-1 (IGF-1) is essential for the pubertal growth spurt and for normal mammary gland development. IGF-1 increases premenopausal breast cancer risk. Oral contraceptives (OCs) decrease IGF-1 in most women. The end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…More than the metabolism of environmental carcinogens, GST gene products are also involved in estrogen metabolism (Henningson et al, 2010). So, variations in GST genes may be relevant in a condition of long-term exposure to synthetic estrogens, such as those observed in oral contraceptive users.…”
Section: Discussionmentioning
confidence: 99%
“…More than the metabolism of environmental carcinogens, GST gene products are also involved in estrogen metabolism (Henningson et al, 2010). So, variations in GST genes may be relevant in a condition of long-term exposure to synthetic estrogens, such as those observed in oral contraceptive users.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research, which supports our results, identified GSTM1 CNVs and sex hormones as two factors that were associated with liver inflammation and carcinogenesis. GST polymorphisms were found to influence the efficiency of estrogen metabolism in women (25).…”
Section: G S T M 1 a N D G S T T 1 G E N E S A R E I N V O L V E D I mentioning
confidence: 99%
“…The level of endogenous estrogen has reportedly been positively associated with igf-1 expression 15 . Estradiol might elevate growth hormone-mediated expression of igf-1 messenger rna in normal mammary tissue by a factor of 4-6 and elevate igf-1 bioactivity by downregulating igfbp-3 synthesis 16 .…”
Section: Introductionmentioning
confidence: 99%